Effect of crumb rubber production technology on performance of modified bitumen. (10th December 2018) - Loderer, C.; Partl, M.N.; Poulikakos, L.D.
Graphical abstract: Highlights: CR blending properties with bitumen are highly influenced by the production process of CR. High pressure water jet technology produces CR with rougher and larger surface area. Larger rubber particle size (<1000 µm) increased the cold temperatures ductility. CR increased modulus at higher temperatures and lowered it at lower temperatures. Abstract: The quality of the bitumen modified with crumb rubber (CR) largely depends on the process parameters when blending CR with bitumen. The larger the specific surface of the CR particles, the better the final properties of the CR-modified bitumen. A novel high-pressure water jet (WJ) based technology has been shown to produce CR with a rougher and larger surface area compared to other traditional techniques such as mechanical shredding (ME) or cryogenic processing (CG). This, in turn, resulted in superior low temperature properties when used as modifier in bitumen. Specifically, the results showed a clear tendency of WJ technology to improve the strength in fracture toughness tests at −10 °C more so than CG and ME. The larger rubber particle size (<1000 µm) the higher the ductility of the material investigated showing improved performance under cold temperatures. From the rheological analysis, it can be concluded that addition of CR to bitumen increases the complex modulus at high temperatures and reduces stiffness at low temperatures. In comparison to SBS polymer modified bitumen there is a flattening of the complex modulus curve indicating less temperature susceptibility. This implies enhanced rutting resistance at high temperatures and enhanced low temperature cracking resistance at low temperatures for CR modified bitumen compared to neat and SBS modified bitumen.